Higher Education in the World 7 Humanities and Higher Education: Synergies between Science, Technology and Humanities - Caamaño Morúa, Carmen (2019)
The system of university disciplines and the fragmentation of its profession–oriented academic results and processes have meant that the management of new knowledge, the synergy between the humanities, science and technology, the interdisciplinary organization of the curriculum, governance structures and the representation of its main actors and communities have not been the prevailing trend. The dominant form of university is still that with a strong identity and historic roots that is closely tied to the student protests and historical contexts of the different countries, especially the legacy of the 1918 Student Reform Movement, which arose at the University of Córdoba, Argentina, and spread to most universities across the region. This mood still prevails today and the affinity remains strong. This paper not only emphasizes the historical and current context of reference, but also presents a set of emerging/converging concepts that are under debate in the Latin American and Caribbean region, with major changes in the way that science and technology are seen from the perspective of humanities, in terms of new paradigmatic, epistemic and intercultural platforms and prefigurations that have arisen at a significant number of Latin American universities.